Individual quality of life and the environment - towards a concept of livable areas for persons with disabilities in Poland - Izabela Grabowska; Radosław Antczak; Jan Zwierzchowski; Tomasz Panek (BMC, 2021)
Abstract Background The United Nations Convention on the Rights of Persons with Disabilities [1] highlights the need to create proper socioeconomic and political conditions for persons with disabilities, with a special focus on their immediate living conditions. According to the Convention, these conditions should be built to ensure that persons with disabilities have the potential to enjoy a high quality of life (QoL), and this principle is reflected in the notion of livable areas. The crucial aspect of this framework is the relationship between the individual QoL and the environment, broadly understood as the socioeconomic as well as the technical conditions in which persons with disabilities function. Methods The basic research problem was to assess the relationship between individual QoL for the population with disabilities as a dependent variable and livability indicators as independent variables, controlling for individual characteristics. The study used a dataset from the EU-SILC (European Union Statistics on Income and Living Conditions) survey carried out in 2015 in Poland. The research concept involved several steps. First, we created a variable measuring the QoL for the entire population with disabilities. To measure the multidimensional QoL, we used Sen's capability approach as a general concept, which was operationalized by the MIMIC (multiple indicators multiple causes) model. In the second step, we identified the livability indicators available in the official statistics, and merged them with survey data. Finally, in the last step, we ran the regression analysis. We also checked the data for the nested structure. Results We confirmed that the general environmental conditions, focused on creating livable areas, played a significant role in shaping the QoL of persons with disabilities; i.e., we found that the higher the level of the local Human Development Index, the higher the quality of life of the individuals living in this area. This relationship held even after controlling for the demographic characteristics of the respondents. Moreover, we found that in addition to the general environmental conditions, the conditions created especially for persons with disabilities (i.e., services for this group and support for their living conditions) affected the QoL of these individuals. Conclusions The results illustrate the need to strengthen policies aimed at promoting the QoL of persons with disabilities by creating access to community assets and services that can contribute to improving the life chances of this population.